Follow-up care needs and motivational factors for childhood cancer survivors and their parents in Germany - Ekaterina, Aleshchenko; Thorsten, Langer; Gabriele, Calaminus; Juliane, Glogner; Kathrin, Hellwig; Pietro, Trocchi; Enno, Swart; Katja, Baust (Scientific reports, 2025)
This study aims to explore the long-term follow-up needs and motivations of childhood and adolescent cancer survivors and their parents to attend follow-up care in Germany, given the inconsistent adherence to national follow-up guidelines. We developed interview guidelines based on the Theory of Planned Behavior and the stereotype priming model to explore motivations and barriers related to follow-up care. We conducted a total of 36 episodic narrative interviews with adolescent (ages 13–17) and adult (ages 18–45) survivors of pediatric cancer, as well as their parents. We analyzed the transcripts qualitatively using thematic content analysis, while quantitative analysis through multiple regression models was used to support the qualitative findings and identify predictors of follow-up care attendance. We identified key themes across age groups, including a strong need to “return to normal life” and a desire for ongoing organizational and social support. Both survivors and parents highlighted specific needs, including timely, personalized health information and practical help with healthcare logistics. Adolescents particularly valued emotional support from their social circles, whereas adult survivors and parents expressed a need for more structured psychosocial and logistical assistance. The findings suggest that both age and the time elapsed since diagnosis play a role in affecting survivors’ perceived control to attend guideline-based follow-up care. Our findings suggest that a differentiated approach to follow-up care, with age-appropriate support structures, and tailored guidelines, may improve adherence among survivors and their parents. To enhance follow-up care adherence among cancer survivors, healthcare providers could offer tailored, age-specific information and practical assistance with healthcare logistics. Additionally, providing emotional and psychosocial support resources for both survivors and their parents can help address their unique needs at different stages of recovery. Trial registration : Registered at German Clinical Trial Register (ID DRKS00025960 and DRKS00026092).